The Implementation of Differentiated Instruction Strategy in P5 Learning at SMK Negeri 1 Jambi - Sakti, Budi Prasetyanto Hari; Putimasurai, Putimasurai (PPSDP International Journal of Education, 2023)
The purpose of this study is to determine the implementation of P5 activities as a project to strengthen the value of Pancasila in the Student’s profile in a school and the impact of its implementation on students. The method used is a qualitative method with a descriptive approach. The data collection technique used was interviews with 2 informants, namely 1 P5 coordinator teacher who developed the module and coordinated the activities, 1 P5 facilitator teacher who taught class X by implementing Merdeka curriculum, and 2 class X students as P5 activity participants. In implementing Merdeka curriculum, students are required to create or carry out a project. One of the project activities in Merdeka curriculum is carrying out P5 activities. The P5 activity is a project activity to strengthen the profile of moral value in Pancasila as students. The P5 activities carried out are adjusted to the seven themes set by the Ministry of Education and Culture. The project results that displayed in this P5 activity are: (1) posters; (2) Short stories; (3) Poetry musical; (4) songs; (5) vlogs; (6) Dramas and (7) Academic writing.